2023
DOI: 10.18699/vjgb-23-10
|View full text |Cite
|
Sign up to set email alerts
|

Changes in DNA methylation profile in liver tissue during progression of HCV-induced fibrosis to hepatocellular carcinoma

Abstract: In this study we compared methylation levels of 27,578 CpG sites between paired samples of the tumor and surrounding liver tissues with various degrees of damage (fibrosis, cirrhosis) in HCV-induced hepatocellular carcinoma (HCC) patients, as well as between tumor and normal tissue in non-viral HCC patients, using GSE73003 and GSE37988 data from GEODataSets (https://www.ncbi.nlm.nih.gov/). A significantly lower number of differentially methylated sites (DMS) were found between HCC of non-viral etiology and nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The present study detected higher methylation levels of ELF3 and ELF5 in primary tumor tissues compared with those in normal tissues. Notably, ELF4 methylation has previously been reported to be significantly upregulated during liver cell carcinogenesis ( 32 ), and hypermethylation of the ELF4 promoter region in colitis preparations has been associated with disease progression to colorectal cancer ( 33 ). However, no significant difference was observed in the methylation level of ELF4 between ccRCC tissues and normal tissues in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The present study detected higher methylation levels of ELF3 and ELF5 in primary tumor tissues compared with those in normal tissues. Notably, ELF4 methylation has previously been reported to be significantly upregulated during liver cell carcinogenesis ( 32 ), and hypermethylation of the ELF4 promoter region in colitis preparations has been associated with disease progression to colorectal cancer ( 33 ). However, no significant difference was observed in the methylation level of ELF4 between ccRCC tissues and normal tissues in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In hepatocellular carcinoma (HCC), the understanding of epigenetic abnormalities linked to aberrant enhancers provides novel insights into drug therapy for this malignancy. It has been observed that DNA methylation can finely tune gene expression by balancing the effects of transcriptional inhibition and activation, highlighting its role in gene repression ( Goncharova et al, 2023 ).…”
mentioning
confidence: 99%